2021
DOI: 10.3390/su13042292
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Conditions Supporting Sustainable Development of Enterprises on Local Level

Abstract: Micro, small and medium enterprises (MSMEs) represent more than 99% of enterprises in Europe. Therefore, knowledge about this sector, also in the spatial context is important to understand the patterns of economic and social development. The main goal of this article is an analysis of spatial conditions and the situation of MSMEs on a local level using combined sources of information. This includes data collected in the Social Insurance Institution and Tax registers in Poland, which provides information on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Kohonen networks have many applications across fields-pattern recognition, medical applications, telecommunications, robotics, product management, data mining and processing or macroeconomic analysis of regions and countries [22][23][24].…”
Section: Methods Of Grouping Objects Into Sets Of Similar Objectsmentioning
confidence: 99%
“…Kohonen networks have many applications across fields-pattern recognition, medical applications, telecommunications, robotics, product management, data mining and processing or macroeconomic analysis of regions and countries [22][23][24].…”
Section: Methods Of Grouping Objects Into Sets Of Similar Objectsmentioning
confidence: 99%
“…Specifically, the principle of the comprehensive evaluation method is to calculate a composite score for each company's indicator based on the standardized processed data after the entropy weighting method determines the weight of each evaluation indicator. The development sustainability factor for the st sample is: (15) Where . is the corresponding index for the th sample in the rd subsystem.…”
Section: Comprehensive Sustainable Development Evaluation Methodsmentioning
confidence: 99%
“…There have been preliminary studies on these issues by many scholars. The literature [15] found that micro, small, and medium-sized enterprises account for more than 99% of European enterprises. Understanding this sector in a spatial context is crucial for understanding economic and social development patterns.…”
Section: Introductionmentioning
confidence: 99%